PEMBERDAYAAN MASYARAKAT DAN PENDIDIKAN KESEHATAN MELALUI KKN KEDISIPLINAN UNMUH BABEL : SOSIALISASI PHBS DAN KEGIATAN SOSIAL DI DESA TANJUNG PURA - Saputra, Adi; Gymnastiar, Abdullah; Febri, Febri; Oktariani, Abbelian; Intrisca, Anggun; Pratiwi, Wulan Oktarina; Fauziah, Selvi; Arsuni, Arsuni; Adawiyah, Nur Robiatul; Sellin, Sellin; Salsabila, Salsabila (Yayasan Education and Social Center, 2025)
Community Service (KKN) is a form of student service to the community through the KKN Discipline Program of the Muhammadiyah University of Bangka Belitung in Tanjung Pura Village focusing on community empowerment and health education through the socialization of PHBS (Clean and Healthy Lifestyle Patterns) and social activities. This abstract summarizes the implementation of the program, its impact on increasing awareness and practice of PHBS in the community, and the contribution of social activities in strengthening partnerships between students and the community of Tanjung Pura Village. The results show an increase in understanding and implementation of PHBS, as well as the establishment of positive and sustainable relationships between students and villagers. This program is an effective model in combining community empowerment with health education in rural areas.